Bioactive non-sterol triterpenoid from Streblus asper: microwave-assisted extraction, HPTLC profiling, computational studies and neuro-pharmacological evaluation in BALB/c mice. (1st November 2016) - Verma, Vandana; Tripathi, Avinash C.; Saraf, Shailendra K.
Abstract: Context : In folk medicine, the stem bark of Streblus asper Lour. (Moraceae) has been reported to possess anticonvulsant activity. However, no systematic/scientific validation is available. Objective This study explores the constituents in the stem bark, their biosassy-guided isolation and their efficacy in neuro-pharmacological disorders, for validating the traditional claims. Materials and methods : Microwave-assisted extraction (MAE) technique was employed to obtain the crude extract. The n -hexane, dichloromethane and aqueous fractions were prepared and phytoconstituents were ascertained by phytochemical tests. The isolated compound, betulin, was characterized by different physicochemical and spectral methods, including HPTLC. Finally, neuro-pharmacological evaluations were conducted at 100, 200, 400 mg/kg b.w., p.o. (25, 50, 100 mg/kg b.w. for betulin) doses in BALB/c mice. Results : The n -hexane fraction (400 mg/kg), and isolated compound betulin (100 mg/kg), showed maximum anticonvulsant activity in maximal electroshock (87.84% and 85.14% seizure inhibition), and isoniazid induced convulsion models (88.85% and 83.18% seizure inhibition), respectively. A dose-dependent attenuation of epileptic seizures was observed, probably through GABArgic mechanism of anticonvulsant action. Moreover, the antidepressant study was also conducted using behavioural models and the results expound that n -hexane and dichloromethane fractions (400 mg/kg) significantly reduced the duration of immobility, as compared to the control. Discussion and conclusion : This study reports some novel aspects like applying an environmentally benign/green approach of MAE, neuro-pharmacological screening and use of docking studies, for the first time, on the plant S. asper . The findings present a rational explanation for its use in traditional medicine, for the management of neuro-pharmacological disorders.